Exploring Local Wisdom In Students’ Writing: Reflecting High Order Thinking Skills In Developing Material Design - Lilla Musyahda (Universitas Muhammadiyah Surabaya, 2019)
Achievement tests are often written by the teachers and given to the students to see how well they are doing. Ideally, they should reflect progress not a failure. They have to reinforce the learning that has taken place, not go out of their way to expose weakness. Meanwhile, the class of Writing has some obstacles in gaining the ultimate goal. Therefore, the writer would like to tailor an instruction which views the class as end product tasks in the framework of High Order Thinking Skills to design language materials for Writing class. The main idea of this study concerns the ability of the language users to pair sentences with the contexts. It reflects the cultural values that can be explained and made sense of independently established cultural priorities. It is an approach which emphasizes the construction of end product as the main thing to be focused on. It stresses that writing is re-writing, re-vision, seeing with new eyes has a central role to play in the act of creating text. In addition, it also increases students’ awareness of alternative ways of studying, and explore their ability in expressing their idea in different cultural context. The context-description of students’ works refer to knowledge of appropriate subject matter in which it promotes the value of local wisdom. It will then be assessed with holistic rubrics which all criteria are evaluated at the same time to see the progress of the learners. Key words: end-product tasks, materials design, high order thinking skills, cultural context.